Penentu Kepatuhan Pajak UMKM Telur Asin Melalui Kualitas Laporan, Pengendalian Internal, dan Mediasi Kinerja Usaha - Hana Selfia; Melvin Rahma Sayuga Subroto; Zulfatun Ruscitasari (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the effect of financial statement quality and internal control systems on the tax compliance of salted egg MSMEs in Brebes Regency, with business performance as a mediating variable. The research employed a quantitative approach using primary data collected through questionnaires distributed to 150 respondents selected through purposive sampling techniques. Data analysis was conducted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The results indicate that the quality of financial statements has a positive and significant effect on business performance, but a negative and significant effect on MSME tax compliance. Meanwhile, the internal control system does not significantly affect business performance, but has a positive and significant effect on tax compliance. Business performance is also proven to have a positive and significant effect on tax compliance and is able to mediate the effect of financial statement quality. These findings provide an important contribution by showing that high-quality financial statements support business operational management; however, tax assistance and guidance are still needed so that these reports can effectively improve tax compliance.